The Urbanisation of the Sea From Concepts and Analysis to Design - Couling, Nancy; Hein, Carola (TU Delft Open, 2020)
The book tells the story of the sea-land continuum based on the case of the North Sea - one of the world's most industrialised seas, in which the Netherlands plays a central role. The space of the North Sea is almost fully planned and has been loaded with the task of increased economic production from new and traditional maritime sectors. At the same time, it has been emptied of cultural signi ficance. Through diverse projects from academia, art, literature, and practice, from analysis to design, the book explores synergies for designing this new spatial realm. Port city expert Carola Hein, professor of the history of architecture & urban planning at Delft University of Technology, and Nancy Couling, associate professor at the Bergen School of Architecture and researcher of the urbanised sea, combine forces with interdisciplinary experts to guide the reader through this complex and fascinating topic.